The Association of Gastropods and Seagrass in Coastal Waters of Beruk Island of North Rupat of Riau Province - Darul Amin; Zulkifli '; Elizal ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This study was conducted in July 2013 in the coastal waters of Beruk Island, Riau. This study was aimed to describe the species composition, distribution, density of seagrass and gastropods, its was also directed to know the distribution of gastropods based on the distribution of seagrass. The survey methods was used in this study. The results showed that there were 279 individuals of gastropod. Those consisted of six species, i.e. Strombus urceus, Ellobium sp, Nerita costata, Conus nobilis, Littorina sp, and Gibbula ardens. There were two seagrass species used as habitat by gastropod, i.e. Enhalus acoroides and Halophila ovalis. Distribution patterns of gastropods in Beruk Island were generally uniform, and varied at each station. The analysis showed that C. nobilis found at all stations, this indicated that these waters were suitable for the survival of C. nobilis, as well as the seagrass species of E. acoroides was also found in all stations.Keywords: Asosiasi, Gastropoda, Padang Lamun, Pulau Beruk